Plan de gestión para la ejecución, monitoreo y control del Proyecto “Construcción del Edificio de Investigación y Desarrollo de la Universidad Estatal a Distancia” de la empresa constructora Estructuras S.A. - Ugalde-Elizondo, Karen (Instituto Tecnológico de Costa Rica, 2016)
In 2015, the construction of the Research and Development Building for the Universidad Estatal a Distancia was granted to Estructuras S.A. Enterprise, through the international tender number EDU-UNED-4-LPI-O-2015LPI-000001, on which basis stablises a set of requirements that make indispensable the application of project management tools. Estructuras S.A. is an organization with experience in the construction sector. However, it does not have standardized practices in project management. This graduation’s final project proposes a Management Plan for the construction project execution, based in the analysis of the enterprise actives related to management project, and the requirements stablished by the tender. The management plan comprises 11 knowledge areas or subject groups, which are, integration, scope, time, cost, quality, human resources, communications, risk, stakeholders, occupational security and, environment. Based on the analysis results, it develops in each area templates or procedures, with the objective of make easier the tasks and solve the requirements established for the project execution.
Proyecto de Graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica, Área Académica de Gerencia de Proyectos, 2016.
Keywords: Administración; Proyectos; Organización; Procesos; Research Subject Categories::TECHNOLOGY::Civil engineering and architecture